Performance Comparison between Nonidentical Segmented Exponential Concave and Nonidentical Segmented Exponential Convex Serrated CATRs. (13th February 2008) - Rama Krishna, T. Venkata; Siddaiah, P.; Rao, B. Prabhakara
Abstract : This paper presented a theoretical and numerical assessment for nonidentical segmented exponential- (NISE-) convex and NISE-concave serrated plane CATRs by changing number of serrations. The investigation was based on diffraction theory and, more specifically, on the diffraction formulation of Fresnel. The compact antenna test range (CATR) provides uniform illumination within the Fresnel region to the test antenna. Application of serrated edges has been shown to be a good method to control diffraction at the edges of the reflectors. In this paper, the Fresnel fields of NISE-convex and NISE-concave serrated CATRs are analyzed using physical optics (PO) technique. The PO analysis is applied in this paper for plane reflector serrated CATR only. The same analysis is applied to any type of reflector. In this paper, lens-based reflector is not considered. It is observed that NISE-concave serrated CATR gives less ripple and enhanced quiet zone width than NISE-convex.